Berenstain Bears (The) / : and the Truth - Berenstain, Stan (New York : Random House, 1983)
Brother and Sister Bear learn how important it is to tell the truth after they accidentally break Mama Bear's most favorite lamp.
Keywords: Honesty--Fiction; Bears--Fiction